The effect of TiO2 nanoparticles size on Cd (II) removal by the paddy crusts from waterbody. Issue 3 (June 2022) - Song, Huijuan; Kuang, Xiaoling; Wei, Xiangdong; Luo, Si; Zeng, Qingru; Peng, Liang
Abstract: The influence of nanoparticles (NP) on the accumulation of heavy metals in the paddy crust (PC) was unclear. This experiment explored the potential effects and mechanism of TiO2 NP with different particle sizes on Cd removal by PC from waterbody. All the TiO2 with size of 25 nm (T25), 100 nm (T100) and 2000 nm (T2000) can promote the Cd uptake by the PC, and with the sequence: T100 > T25 > T1000. Especially, 0.1 mg/L T100 can enhanced ~45% Cd removal comparing with pristine PC, and the Cd uptake capacity reached as high as 92 mg/g. After treatment of 72 h, the PC+T100 can reduce Cd in the acidic coal drainage from 0.48 mg/L to 0.009 mg/L, with removal efficiency of 98%. The total concentration of surface adsorptive site number of PC+T100, PC+T25 and PC was 0.87 ± 0.03, 0.78 ± 0.07 and 0.67 ± 0.04, respectively. The TiO2 stimulation to PCs secreted the extracellular substance and then increased the content of amino/hydroxyl adsorptive sites by 30–70%. T100 can stimulate high EPS-producing algae and bacteria, whereas most T25 can only penetrate the cell walls of low EPS-producing microorganisms. T100 can stimulate not only the thick sheath layer of Oedogonium, the main component of PC, but also the thin layer of algae and bacterium. And induce it to produce a large amount of protein, phospholipids, etc. T25 can only stimulate the Microcystics, Chlorococcum, Scenedesmius and bacteria with thin cell membranes to produce low extracellular substance. However, T25 would easily enter the cell trough thin cell membranes, result in that the Cd attached to T25 to penetrate the intracell. Therefore, the non-EDTA-exchangeable Cd fraction in PC+T25 was 55.48%, higher than 36.82% of PC+T100, and 21.52% of PC. Our investigation demonstrated that the addition of TiO2 NP with appropriated size in PC was a potential efficient method to remove the heavy metal from waterbody. Graphical Abstract: ga1 Highlights: Anatase TiO2 -NP with different size can promote PC to uptake Cd, and the improving effect was T100 > T25 > T2000. The PC+T100 can reduce Cd in the acidic coal drainage from 0.48 mg/L to 0.009 mg/L. The T100 induce the adsorptive site number in PC was larger than that of T25. T25 easily enters the algae and microbial cells inducing the Cd into intracell.